Therapeutic Dose of Hydroxyurea-Induced Synaptic Abnormalities on the Mouse Spermatocyte - Fan, Xiaobo; Zhu, Yunxia; Wang, Naixin; Zhang, Bing; Zhang, Cui; Wang, Yanan (Frontiers in Physiology, 2021)
Hydroxyurea (HU) is a widely used pharmacological therapy for sickle cell disease (SCD). However, replication stress caused by HU has been shown to inhibit premeiotic S-phase DNA, leading to reproductive toxicity in germ cells. In this study, we administered the therapeutic doses of HU (i.e., 25 and 50 mg/kg) to male mice to explore whether replication stress by HU affects pachytene spermatocytes and causes the abnormalities of homologous chromosomes pairing and recombination during prophase I of meiosis. In comparison with the control group, the proportions of spermatocyte gaps were significantly different in the experimental groups injected with 25 mg/kg (p < 0.05) and 50 mg/kg of HU (p < 0.05). Moreover, the proportions of unrepaired double-stranded breaks (DSBs) observed by γH2AX staining also corresponded to a higher HU dose with a greater number of breaks. Additionally, a reduction in the counts of recombination foci on the autosomal SCs was observed in the pachytene spermatocytes. Our results reveal that HU has some effects on synaptonemal complex (SC) formation and DSB repair which suggest possible problems in fertility. Therefore, this study provides new evidence of the mechanisms underlying HU reproductive toxicity.